Accreditation and evaluation in the European higher education area (Kluwer Academic, 2004)
This volume presents a rich account of the development of accreditation and evaluation in 20 European countries. The authors are leaders in the field and they have cooperated in this effort by writing richly different, often deep and insightful analyses of the situation in their country. The two editors have added a synopsis detailing the main trends, and sketching commonalities as well as contrasts in the developments across Europe. The book shows how accreditation is becoming a main mechanism in the steering of higher education all over Europe. The book is unique in its analysis of forces driving towards the spread of different models of accreditation in the emerging European Higher Education area. Readers will obtain an up-to-date picture of the state of affairs of accreditation in the framework of evaluation activities in Europe. They will gain an understanding of why accreditation and evaluation systems have evolved the way they have, and subsequently, they will obtain more realistic views on potentialities for European comparability and cooperation in this area.